Avtobiografskost kot umeščanje osebne izkušnje - Tratnik, Suzana (Jezik in slovstvo, 2008)
In the article I consider whether lesbian and gay literature is necessarily autobiographical and reflect on the meaning of putting personal experience into literature for this kind of writing. In this literature the autobiographyis frequently regarded as weaker in a literary sense, because it is thought that the authors write "simply from within themselves". However, with the structuring of personal experience in the broader social context these experiences gain a location, while lesbian/gay writing shows itself as a platform for creativity and a broader perspective of the writer.
Keywords: avtobiografije; gay literature; gejevska književnost; homoerotična književnost; lezbična književnost; Slovene literature; slovenska književnost